Numerical integration-based algorithm for efficient actual navigation performance of airborne integrated navigation systems - Wang, Chonggeng; Zhong, Lunlong (Chinese Control and Decision Conference, 2024)
Flight management system is one of the core technologies of avionics system for large civil aircraft. Among them, the integrated navigation system is the core component of the flight management system, supporting trajectory prediction, autopilot, flight guidance and other key functions. The actual navigation performance (ANP) can reflect the navigation performance of the integrated navigation system at the current moment. Under the performance based navigation (PBN) mode of operation, a fast and accurate calculation of ANP is indispensable for the navigation and positioning solving and navigation mode management of the integrated navigation system of an airplane, and the key to the calculation of ANP lies in the accuracy and fastness of the calculation. Aiming at the above problems, the two-dimensional normal distribution characteristics of the position error of the integrated navigation system are studied, and an ANP evaluation model based on the two-dimensional error probability density function is established. The ANP evaluation process is simplified into a probability calculation problem. An efficient ANP algorithm for airborne integrated navigation systems based on numerical integration is proposed, which adopts Gauss Legende's efficient numerical integration method to accelerate the computation speed of the dual integration, and at the same time optimizes the existence interval of ANP based on the error distribution characteristics, and adopts the bisection iterative method to quickly compute the ANP value of the integrated navigation system within the interval. The simulation results show that compared with the traditional algorithm, the Gauss Legende numerical integration-bisection iteration algorithm greatly reduces the computation time and improves the computation efficiency while guaranteeing the accuracy, providing reliable support for the integrated navigation system of the aircraft to carry out the functions of navigation and positioning solving and navigation mode management.